1997
DOI: 10.1111/j.1600-0420.1997.tb00406.x
|View full text |Cite
|
Sign up to set email alerts
|

Eye size in healthy Swedish children and in children with fetal alcohol syndrome

Abstract: ABSTRACT.Purpose: This study set out to collect reference data for normal ocular growth and to study the teratological effects of alcohol on eye development. Methodc Eye size was studied in 92 healthy Swedish children (age 1 month to 16 years) as reference and in 13 children (age 1.4 months to 17 years) with fetal alcohol syndrome (FAS) using ultrasonographic axial length measurements. Another three children with FAS were evaluated by clinical examination only. Results:The control group demonstrated a marked i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 33 publications
0
14
0
1
Order By: Relevance
“…There are no significant differences in gene expression of alcohol dehydrogenases (ADH), catalase, and a number of the cytochrome P450 enzyme family between B6 and D2 mice; aldehyde dehydrogenase 2 (ALDH2) and aldehyde dehydrogenase 1A1 (ALDH1A1) are higher in D2, whereas aldehyde dehydrogenase 7A1 (ALDH7A1) is higher in B6 (Bhave et al, 2006). One report indicated that hepatic and brain catalase activities were two- to three-fold higher in adult D2 than in adult B6 mice (He et al, 1997). Alcohol dehydrogenase 3 (ADH3) is a major form of alcohol catabolic enzyme in embryonic alcohol metabolism (Duester, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…There are no significant differences in gene expression of alcohol dehydrogenases (ADH), catalase, and a number of the cytochrome P450 enzyme family between B6 and D2 mice; aldehyde dehydrogenase 2 (ALDH2) and aldehyde dehydrogenase 1A1 (ALDH1A1) are higher in D2, whereas aldehyde dehydrogenase 7A1 (ALDH7A1) is higher in B6 (Bhave et al, 2006). One report indicated that hepatic and brain catalase activities were two- to three-fold higher in adult D2 than in adult B6 mice (He et al, 1997). Alcohol dehydrogenase 3 (ADH3) is a major form of alcohol catabolic enzyme in embryonic alcohol metabolism (Duester, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Intercorrelated diagnoses of prematurity and LBW ⁄ SGA, as well as prenatal alcohol-related diseases (e.g. FAS) have been shown to be associated with a range of ophthalmic morbidities (Stro¨mland 1985;Hellstro¨m et al 1997Hellstro¨m et al , 2000Hellstro¨m et al , 2004Holmstro¨m et al 1998Holmstro¨m et al , 1999Vohr et al 2000;O'Connor et al 2002;Larsson 2004). Preterm children have a higher risk of developing refractive errors than children born full-term (Holmstro¨m et al 1998;Larsson 2004).…”
Section: Discussionmentioning
confidence: 99%
“…A variety of physical measurements are used in the evaluation of children with dysmorphic features and ⁄ or structural anomalies. Among these are the measurements of eye structures such as total ocular axial length (TAL) (Hellstro¨m et al 1997), inner canthal distance (ICD) and palpebral fissure length (PFL) (Hall et al 1989).…”
Section: Introductionmentioning
confidence: 99%
“…No Brasil, estima-se que 6/ 1000 mulheres façam uso de álcool durante a gestação (9) . As alterações encontradas neste grupo de indivíduos são comuns às manifestações oftalmológicas da síndrome alcoólica fetal (SAF), tais como: epicanto, filtro nasal hipoplásico, base nasal alargada, achatamento da face média, baixa acuidade visual, hipoplasia do nervo óptico, miopia e ptose, em associação com uso de álcool durante a gestação (9,(14)(15)(16)(17)(18)(19)(20)(21)(22) . Porém, não foi confirmado nenhum caso de SAF dentre os indivíduos da amostra estudada, uma vez que não apresentavam os critérios diagnósticos para a síndrome completa, que incluem retardo do crescimento pré ou pós-natal, envolvimento do sistema nervoso e dismorfismo facial, além da história de uso de álcool durante a gestação.…”
Section: Discussionunclassified